The Role of Customer Psychology in Solving E-Commerce Problems - R Billewar, Satish; P Pande, Amol; N Kolhe, Likhesh (International Journal of Psychosocial Rehabilitation, 2020)
Online reviews and ratings have become an integral part of the purchase process which is beneficial not only for the online companies to understand the products but it also impacts customer psychology in buying process. In other words, reviews have real value for customers and people now depend on them. Nevertheless, bad reviews means a lot for improvements in the products and services are needed. Sometimes customer expects the repair facility like a service engineer nearby to his home. The biggest problem is there is no common platform to provide all services of the products. The online companies need to understand the impact of customer’s psychology on the business. The paper suggests the modifications in current E-Commerce system with multiple facilities like unbiased product comparisons before purchase, after sales repair and real time conversations with the customer to sort out other service related issues of any brand.